"Existirmos, a que será que se destina?": trabalho e reconhecimento no tráfico de drogas varejista - Thaísa Vilela Fonseca Amaral (2020)
The objective of this doctoral thesis is to analyze the relationship between labor and social recognition in the retail drug trafficking in Minas Gerais. We started from the following questions: could we affirm the existence of a social function in this labor? How do trafficking activities confer recognition to those in it? How does this recognition operate in the construction of sociability? Under the theoretical-methodological perspective of labor clinics, we seek to answer such questions through an ethnographic approach of labor with the use of interviews, engaged observations and the participation of a co-researcher. We propose a reflection on the nexus between labor and recognition, arguing that the insertion in drug trafficking was made, for the workers we interviewed, as an important passage in the transit between legalities / illegalities, which has the dimension of an event and comes from the experience of helplessness. We will see that before so many contradictions, exploitations, violations and violence in contemporary social life it is in and through the work in drug trafficking that these people find a way to project themselves into the future, to expand the possibilities of living, to seek recognition, to resist, to finally guarantee existence.